Effects of edaravone on hypoxia-induced lethality in male Swiss albino mice - Shaki, Fatemeh; Mokhtaran, Mina; Raei, Maedeh; Razavi, Alireza; Shamshirian, Amir; Eslami, Shahram; Shamshirian, Danial; Ebrahimzadeh, Mohammad Ali (Faculty of Medicine Universitas Indonesia, 2025)
BACKGROUND Edaravone has recently been used to treat acute cerebral infarction. This study aimed to evaluate the protective effects of edaravone against hypoxia-induced lethality and oxidative stress in mice using 3 experimental models of hypoxia: asphyxia, circulatory, and hemic hypoxia. METHODS 60 Swiss albino mice from the animal facility of Mazandaran University of Medical Sciences, Iran, were randomly housed in groups of 10 during January–March 2020 and received edaravone for 4 consecutive days. After inducing hypoxia, oxidative stress, lipid peroxidation (LPO), and glutathione (GSH) content were assessed. RESULTS The findings showed significant protective effects of edaravone in all hypoxia models, with the strongest effects in asphyxia and circulatory hypoxia, showing a dose-dependent response. It prolonged survival time at 2.5 mg/kg by 26.08 (0.79) min (p = 0.031) In addition, edaravone significantly inhibited hypoxia-induced oxidative stress (LPO and GSH oxidation) in all 3 hypoxia models. CONCLUSIONS Edaravone exhibits an excellent protective effect against different models of hypoxia by decreasing oxidative stress in brain tissue. In addition, the results showed dose-dependent effects of edaravone in the asphyxia and circulatory hypoxia models. Antioxidant activity might be a proposed mechanism for the anti-hypoxic activity of this drug.